Effect of pH and calcination temperature on co-precipitated indium oxide nanoparticles / Goh Kian Wei - Goh, Kian Wei (2017)
Indium oxide nanoparticles (In2O3 NPs) were successfully synthesized by coprecipitation method. By using co-precipitation method, indium hydroxide nanoparticles (In(OH)3 NPs) were initially synthesized at various pH values of 8, 9, 10 and 11. The In2O3 NPs were formed by calcining the optimized as-prepared In(OH)3 NPs at various calcination temperatures (200, 300, 400, 500, 600 ℃). Structural characterizations of the samples were performed by thermogravimetric (TGA and DTA) analysis, X-Ray Diffractometer (XRD), Fourier transform infrared spectroscopy (FTIR), Raman spectroscopy, zeta potential measurement, and high-resolution transmission electron microscope (HRTEM). The crystallite sizes of as-prepared In(OH)3 and In2O3 NPs were calculated by Scherrer equation had similar trend with values obtained from William- Hall plot. HRTEM images showed that the particles size of as-prepared In(OH)3 were within the range of 11.76 - 20.76 nm. The maximum zeta potential (3.68 mV) of In(OH)3 NPs associated with the smallest particle size distribution (92.6 nm) were occurred at pH 10. Hence, further work on formation of In2O3 NPs were conducted by calcining the as-prepared In(OH)3 NPs at an optimum pH 10. XRD, Raman, FTIR and thermal studies of the samples revealed that the In(OH)3 NPs were converted completely into In2O3 NPs at 300 ℃. Besides, HRTEM images showed that the particles size of In2O3 NPs was within the range of 14.67 - 27.67 nm. The smallest In2O3 NPs (14.67 nm) with homogenous particle distribution were formed at lower calcination temperature of 300℃. As compare to literatures, this work clearly confirmed that optimized In2O3 NPs could be obtained at pH 10 with a relatively low calcination temperature of 300 ℃ via co-precipitation method.